Malignant bilateral ovarian steroid cell tumor without androgenic manifestation: an unusual finding - Emilia Theresia; Bob Irsan; Ery Kus Dwianingsih; Moh Nailul Fahmi; Heru Pradjatmo; . Irianiwati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2022)
Steroid cell tumor is a rarest ovarian neoplasm, classified as a pure stromal tumor and mostly is unilateral. Even though this tumor can exhibit malignant behavior but the morphology of cells showed benign characteristics which can become a diagnosis pitfall especially in the frozen section. Moreover patient without any hormonal imbalance or virilizing signs could make the diagnosis process more difficult. Here we reported a case bilateral steroid cell tumor of the ovary in a 42 y.o. unmarried woman without any virilization or hirsutism symptoms. Abdominal ultrasonography and computed tomography (CT) scan revealed a right ovarian solid tumor accompanied by ascites and right pleural effusion. There was significantly increased of Ca 125 level (1138 U/mL) and normal level of testosterone (0.10 ng/mL). Frozen section was done from the right ovarium mass and ascites fluid, the result was benign. From the total abdominal hysterectomy and bilateral salpingo-oophorectomy tissues,  histological picture showed diffuse and nests tumor separated by thin fibrous connective tissue with small round centered nuclei, mild atypia, and abundant pale cytoplasm. Large area of necrosis was found especially in the right ovarian tumor, tumor implant to the right fallopian tube and in the uterine serous layer. Periodic acid-Schiff (PAS) stain was negative in more than half tumor cells population. Immunostaining for Melan-A and Calretinin were focally positive, with Ki-67 labeling index ± 5%, and negative for cytokeratin 7 (CK7), cytokeratin 20 (CK20) and smooth muscle actin (SMA). Based on the tumor size, necrosis area, tumor implantation, and immunohistochemistry profiles, we conclude that were malignant steroid cell tumor. Currently, the patient is undergoing postoperative recovery and planned for platinum-based chemotherapy. A careful correlation between clinical and radiological findings, as well as histopathological results, is always essential, as is amply demonstrated by this particular case.